2009
DOI: 10.1007/s11244-009-9414-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nano-Sized Platinum Metal Particles on Ti-Containing Mesoporous Silica Using Microwave-Assisted Deposition Method

Abstract: Using microwave-assisted deposition method the uniform and nano-sized platinum metal particles were prepared on the tetrahedrally coordinated Ti-oxide moieties isolated within the framework of mesoporous silica supports. The present nano-sized metal catalyst exhibited a higher activity for hydrogenation of nitrobenzene than the catalyst prepared by a conventional impregnation method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Ti-containing mesoporous silica was prepared according to a previous report by a sol-gel method using tetraethoxysilane (TEOS: Si(OEt) 4 ) as a silica source, titanium tetraisopropoxide (TPOT: Ti(O i Pr) 4 ) as a titanium source and dodecylamine hydrochloride (DDA: CH 3 (CH 2 ) 11 NH 3 Cl) as a template (Ti-HMS, Si : Ti ¼ 99 : 1). 35 After the Ti-HMS (0.489 g) was suspended in a mixed aqueous solution (20 cm 3 ) of NiSO 4 $6H 2 O (0.023 g) and 50 mM HCl aqueous solution (12 mM, 5 cm 3 ) of PdCl 2 , the pH of the suspension was adjusted to 10 by aqueous ammonia. After bubbling with Ar, the suspension was photoirradiated by a 100 W high-pressure mercury arc for 20 h. After filtration and washing with distilled water, the resultant powder was dried at 373 K overnight and calcined at 723 K for 3 h in air and then reduced by H 2 at 773 K for 60 min, resulting in the formation of PAD-PdNi/Ti-HMS (Ni/Pd ¼ 1.5).…”
Section: Experimental Preparation Of Catalystsmentioning
confidence: 99%
“…Ti-containing mesoporous silica was prepared according to a previous report by a sol-gel method using tetraethoxysilane (TEOS: Si(OEt) 4 ) as a silica source, titanium tetraisopropoxide (TPOT: Ti(O i Pr) 4 ) as a titanium source and dodecylamine hydrochloride (DDA: CH 3 (CH 2 ) 11 NH 3 Cl) as a template (Ti-HMS, Si : Ti ¼ 99 : 1). 35 After the Ti-HMS (0.489 g) was suspended in a mixed aqueous solution (20 cm 3 ) of NiSO 4 $6H 2 O (0.023 g) and 50 mM HCl aqueous solution (12 mM, 5 cm 3 ) of PdCl 2 , the pH of the suspension was adjusted to 10 by aqueous ammonia. After bubbling with Ar, the suspension was photoirradiated by a 100 W high-pressure mercury arc for 20 h. After filtration and washing with distilled water, the resultant powder was dried at 373 K overnight and calcined at 723 K for 3 h in air and then reduced by H 2 at 773 K for 60 min, resulting in the formation of PAD-PdNi/Ti-HMS (Ni/Pd ¼ 1.5).…”
Section: Experimental Preparation Of Catalystsmentioning
confidence: 99%
“…Therefore, it can be considered that titanium moieties within silica matrices interact with microwaves and are heated selectively, resulting in the formation of a heatspot on titanium moieties acting as deposition sites. 33,34 A TEM image also revealed the formation of CNTs on Co-Mo/Ti(10)-MSTF as shown in Fig. 7.…”
Section: Resultsmentioning
confidence: 85%
“…Moreover, our group has reported that metallic particles with a mean diameter of 3-4 nm were successfully formed on Ti-containing mesoporous silica under microwave irradiation. 33,34 Interaction between isolated titanium moieties within the silica frameworks and microwaves enabled the immobilization of highly-dispersed metallic particles on the Ti-sites.…”
Section: Introductionmentioning
confidence: 99%
“…The overidentification of microwave specific effects has been attributed to experimental difficulties in accurately measuring temperature within the reaction vessel. Subsequently, as the technology for accurately determining temperature in the microwave improved, studies of homogeneous reactions were reported that clearly showed microwave specific rate enhancement. …”
Section: Introductionmentioning
confidence: 99%